Electric Power Supply System with Negligible Voltage Asymmetry Coefficient on the Input Side of the Main Traction Transformer - A. B. Kosarev; M. V. Alexeenko (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
The paper tackles the substantiation aspect of the AC traction power supply system (TPSS) allowing reduction to the permissible level in the voltage symmetry coefficient on the input side of the main traction transformer of the AC traction substation. For this purpose it is recommended to insert multifunctional booster transformer in the TPSS. Its input power (main) winding is connected to one of the 27.5 kV-side branches of the main traction transformer, booster winding is brought in the traction substation feeder line and compensating winding is loaded on the adjustable capacitor unit. Data products of analytical calculations, performed by the proposed by the authors analysis procedure of electromagnetic processes in the TPSS with the multifunctional booster transformer, allowed to substantiate the capacitor unit parameters for the case of its energizing to carry the compensating winding’s 2.5 kV. When performing calculations the account was taken of the possible electric locomotive casting in the form of a power source and of a current source as well. While analyzing current distribution within the TPSS with multifunctional boosting transformer the authors used the standard set of equations, formulated by the mesh technique. In the case of current collector conceiving as a power source the necessity of employing iteration procedure was caused by non-linearity of the system under consideration due to quadratic dependence of electric locomotive resistance on the current collector voltage. Similar procedure was also employed in the case of current collector conceiving as a current source. For the case of employing adjustable capacitor unit it was found that according to the law presented in the paper, asymmetry coefficient does not exceed the values set by the GOST 13109-97 while leading and retarding phases’ currents differ from each other in modulus by no more than 30 %. It is noted that with booster winding of the multifunctional booster transformer brought in the traction substation feeder line it becomes possible to increase the retarding phase voltage by the value very near to the EMF induced in the booster winding due to its magnetic interaction with the input power winding and to raise simultaneously the leading phase current by somewhat lower value.